2016
DOI: 10.7567/jjap.55.076502
|View full text |Cite
|
Sign up to set email alerts
|

Bubble-free high-speed UV nanoimprint lithography using condensable gas with very low global warming potential

Abstract: Bubble-free filling needs to be achieved to realize high-throughput mass production in ultraviolet nanoimprint lithography (UV-NIL). Although bubble-free filling can be accomplished by performing UV-NIL under vacuum, nonvacuum processes can lower equipment and operation costs. UV-NIL in 1,1,1,3,3-pentafluoropropane (PFP) has been recognized as a promising method of realizing ultrahigh-speed UV-NIL; however, the global warming potential (GWP) of PFP of 1030 might restrict its industrial use. In this work, UV-NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…As the cause of this, we considered that the patterns were stretched and collapsed owing to the problem in mold release. As reported in previously [18,20], the average release force following UV-NIL in CTFP was approximately 14% smaller than that after UV-NIL in PFP and TFP. From these results of the patterning of PAK-02 with nominal 22 nm 1:3 L/S pattern, it was considered that a condensable gas atmosphere should be introduced with mixed gases of TFP/CTFP rather than only an atmosphere of TFP.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As the cause of this, we considered that the patterns were stretched and collapsed owing to the problem in mold release. As reported in previously [18,20], the average release force following UV-NIL in CTFP was approximately 14% smaller than that after UV-NIL in PFP and TFP. From these results of the patterning of PAK-02 with nominal 22 nm 1:3 L/S pattern, it was considered that a condensable gas atmosphere should be introduced with mixed gases of TFP/CTFP rather than only an atmosphere of TFP.…”
Section: Resultssupporting
confidence: 80%
“…The amount of gas dissolution in the solvent was corrected by subtracting the volatilization amount for 10 minutes in air. The number of solvents with a gas dissolution of over 2% were 16,18, and 13 for PFP, CTFP, and TFP, respectively. In particular, it was found that large quantities of gas dissolution were observed in acetone, dimethyl formamide, and tetrahydrofuran.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this small mold requires a high-precision calibration system to complete the imprinting process, which increases the processing cost. 107 Compared with plate imprinting, the roller imprinting method can significantly expedite the imprinting process. Besides, the linear contact between the roller mold and the resist film during the imprinting and demolding process substantially reduces the problems seen in plate imprinting, including uneven force exerted on the mold and the unevenness of the substrate, thereby avoiding the generation of bubbles.…”
Section: Fabrication Process Of R-nilmentioning
confidence: 99%
“…Therefore, to fabricate ceramic micro-pillar patterns, our study focused on UV nanoimprint lithography (UV-NIL), which can produce nano-and microstructures on a resist polymer using a UV-curable polymer. [25][26][27][28][29] The UV-NIL technique has attracted attention in micro-electronic fields such as large-scale integrated circuit (LSI) and MEMS fabrication owing to its advantages in high-aspect-ratio fabrication [30][31][32] by directly molding the liquid resin on a substrate, unlike the hot embossing process that molds a solid material. To the best of our knowledge, no reports on a UV-NIL process to fabricate high-aspect-ratio GDC micro-pillar patterns have been made.…”
Section: Introductionmentioning
confidence: 99%